Effect Of Health Education Model BASNEF On Knowledge And Compliance With Hypertension Diet In Elderly With Hypertension - Setyoadi; Sari, Efris Kartika; Larasati, Intan (Al-Hijrah Indonesia, 2023)
Hypertension is a disease that mostly affects the elderly, this is due to unhealthy lifestyle changes, easy fast food, and excessive salt and fat consumption. Poor knowledge and adherence to the hypertension diet make the elderly not follow the hypertension diet properly. This study aimed to analyze the effect of the BASNEF model of health education on dietary knowledge and adherence in elderly people with hypertension. This study used Quasi-experimental one group pre-test and post-test design. The study population was elderly with hypertension taken by purposive sampling method, a total of 40 people with the criteria of being able to read, carry out activities independently, and live with family. The instrument used to measure variables is a questionnaire and data were analyzed using the Wilcoxon test. The average value obtained for knowledge of the hypertension diet increased by 14.78 and adherence to the hypertension diet also experienced an increase in the average value of 44.53. The results of the Wilcoxon test showed that there was an effect of the BASNEF model of health education on knowledge and adherence to the hypertension diet in elderly people with hypertension which was significant with p<0.05. The BASNEF method of health education can be an alternative to increasing knowledge and adherence to hypertension among elderly people in the community.